2018
DOI: 10.3892/ijmm.2018.3458
|View full text |Cite
|
Sign up to set email alerts
|

The effects of TRAF6 on proliferation, apoptosis and invasion in osteosarcoma are regulated by miR-124

Abstract: The present study aimed to verify tumor necrosis factor receptor‑associated factor 6 (TRAF6) as the target gene of microRNA-124 (miR-124). In addition, the expression of miR‑124 was investigated in osteosarcoma tissues and cells, and its effects on the biological characteristics of osteosarcoma cells were determined, in order to provide an experimental and theoretical basis for the application of TRAF6 in the treatment of osteosarcoma. A fluorescence reporter enzyme system was used to verify TRAF6 as a target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Here, we first validated HOXA-AS2 as a decoy of miR-124-3p in OS cells by luciferase reporter assay, RIP and RNA pull-down analyses. Former works suggested that miR-124, the precursor miRNA of miR-124-3p, could suppress proliferation, migration and invasion of OS by targeting receptor tyrosine kinase-like orphan receptor 2, B7 homolog 3, sphingosine kinase 1 or tumor necrosis factor receptor-associated factor 6 1922. More particularly, miR-124-3p was reported as a tumor suppressor in OS by regulating snail family zinc finger 2 or Rho-associated kinase 1 23,24.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we first validated HOXA-AS2 as a decoy of miR-124-3p in OS cells by luciferase reporter assay, RIP and RNA pull-down analyses. Former works suggested that miR-124, the precursor miRNA of miR-124-3p, could suppress proliferation, migration and invasion of OS by targeting receptor tyrosine kinase-like orphan receptor 2, B7 homolog 3, sphingosine kinase 1 or tumor necrosis factor receptor-associated factor 6 1922. More particularly, miR-124-3p was reported as a tumor suppressor in OS by regulating snail family zinc finger 2 or Rho-associated kinase 1 23,24.…”
Section: Discussionmentioning
confidence: 99%
“…miR-643 has recently been proved to targeting TRAF6 in human endometrial epithelial cells (HEECs) that significantly reduces the expression of TRAF6 [78]. miR-124 has also been reported to be related to negative regulation of TRAF6 expression in human osteosarcoma cells and colorectal cancer cells [79,80].…”
Section: The Regulation Of Traf6 By Expressionmentioning
confidence: 99%
“…3) suggesting that MIR124 is dysregulated in BBM. Recent studies have reported that MIR124-2 suppresses proliferation, aggressiveness, apoptosis, and invasion of osteosarcoma 47 , 48 . MIR124 is abundantly expressed in the nervous system where it contributes to regulation of alternative splicing and plays a crucial role in the differentiation of progenitor neuronal cells 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%